1980
DOI: 10.1161/01.res.46.1.117
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tetrodotoxin, lidocaine, verapamil, and AHR-2666 on Ouabain-induced delayed afterdepolarizations in canine Purkinje fibers.

Abstract: SUMMARY We used standard microelectrode techniques to record delayed afterdepolarizations (DAD) induced by ouabain (2 x 1 0 7 M) in isolated canine Purkinje fibers (PF) and studied the response of DAD to the fast Na* channel blocker, tetrodotoxin (TTX, 1 mg/liter); the slow channel blocker, verapamil (verap, 1 mg/liter); the putative Ca 2+ blocker, AHR-2666 (AHR, 45 mg/liter); and lidocaine (lido, 4 mg/liter), which increases steady state outward current and decreases background inward current. PF were driven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(66 citation statements)
references
References 35 publications
5
61
0
Order By: Relevance
“…'7 The measurements of the amplitude and coupling interval of delayed afterdepolarizations were made in a manner similar to that described by Rosen and Danilo. 18 The amplitude was measured from the most negative level recorded during repolarization to the peak positive level reached by the delayed afterdepolarization. The coupling interval was measured from the upstroke of the last driven action potential to the peak positive level of the delayed afterdepolarization.…”
Section: Methodsmentioning
confidence: 99%
“…'7 The measurements of the amplitude and coupling interval of delayed afterdepolarizations were made in a manner similar to that described by Rosen and Danilo. 18 The amplitude was measured from the most negative level recorded during repolarization to the peak positive level reached by the delayed afterdepolarization. The coupling interval was measured from the upstroke of the last driven action potential to the peak positive level of the delayed afterdepolarization.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the response of PEBs to electrical stimulation, we postulate that PEBs are based on triggered activity resulting from delayed afterdepolarizations. This hypothesis was tested in 82 experiments by 1) stimulation under control conditions and in combination with 2) subtoxic and toxic amounts of ouabain 20-50 jig/kg, 3) lidocaine 3 mg/kg, and 4) doxorubicin [16][17][18][19][20][21][22][23][24] mg/M2. The stimulation protocol, which was repeated at random five to 10 times, consisted of 10 and 50 stimuli using interstimulus intervals of 200, 400, 600, and 800 msec.…”
mentioning
confidence: 99%
“…Previous studies had shown that lidocaine at therapeutic concentrations suppresses normal automaticity and delayed afterdepolarizations. 22,23 The effects of the drug matrix on mechanisms for normal and abnormal impulse initiation have been studied extensively, as have its effects on conduction.9-12,18,23,26 However, knowledge of its actions on cell coupling, on passive membrane properties, and on threshold for excitability are incomplete. Needless to say, such information would be valuable in furthering our understanding of the actions of the drugs in the matrix.…”
Section: Discussionmentioning
confidence: 99%
“…The Purkinje fibers were impaled with 3 M KCIfilled glass microelectrodes having tip resistances of [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Mfl. Attempts were made to impale the site of earliest impulse initiation, at which the slope of phase 4 and phase 0 merged smoothly in the typical configuration of a pacemaker fiber.…”
Section: Methodsmentioning
confidence: 99%